Comparison of Physical Properties of an Iranian and a German Dental Stone Type IV According to ADA Specifications - Mahmood Sabouhi; Niloofar Khodaeian; Maryam Soltani; Ebrahim Ataei (Islamic Dental Association of Iran, 2013)
Background and Aim: Dental stone type IV and V are predominantly used for construction of cast and die in fixed prosthodontics and must have some special properties. The aim of this study was to compare the three physical properties of an Iranian a German dental stone type IV .   Materials and Methods: In this experimental study, setting time, setting expansion and compressive strength properties were evaluated according to ADA specification No.25for Iranian Tara and German Gildand type IV dental stone. For setting time, setting expansion and compressive strength tests, Vicat apparatus, extensometer and universal testing machine were used, respectively. Data were compared to ADA specification No.25 for dental stone type IV and statistically analyzed using t-test with a 0.05 level of significance .   Results: Mean of setting expansion for Iranian and German dental stone were 0.024±0.011 and 0.0245±0.009, respectively and were within the limits of ADA specification and there was no statistically significant difference between them (P=0.966). Mean of setting time for Iranian and German dental stone were 44.5±0.70 and 17.29±0.41 and mean of compressive strength for Iranian and German dental stone were 16.17±0.97 and 20.15±1.96 and both specifications were not within the limits of ADA specification, but statistically significant differences were found between groups (P<0.001) .   Conclusion: Iranian dental stone type IV could not fulfill 2 out of 3 tested ADA specification and modification of this stone is necessary for use in fixed prosthodontics laboratory processes .